Application of Extended Health Belief Model in Predicting COVID-19 Preventive Behaviors in Adults: A Web-based Study - Malihe Mobarakian; Homamodin Javadzade; Marzieh Mahmoodi; Mahnoush Reisi (Mazandaran University of Medical Sciences, 2022)
Introduction and purpose: The World Health Organization considers preventive behaviors, which are influenced by several factors, the most important factor in breaking the COVID-19 transmission chain. Therefore, the present study aimed to determine the predictors of COVID-19 preventive behaviors based on an extended pattern of health beliefs in adults. Methods: The present study is a descriptive-analytical cross-sectional study performed on 900 adults. The sample was selected through convenience sampling from the statistical population of Salamooz website users. In this study, information was collected using a researcher-made questionnaire consisting of four sections (demographic characteristics, health belief model constructs, perceived social support, and COVID-19 preventive behaviors) and statistically analyzed using the SPSS software (version 24). Results: Among the studied variables, age (P<0.001, B=0.04), sex (P<0.001, B=1.33), history of COVID-19 (P=0.001, B=-0.75), perceived sensitivity (P=0.007, B=0.13), perceived barriers (P<0.001, B=-0.24), perceived self-efficacy (P< 0.001, B=0.16), family social support (P<0.001, B=0.13), and friends social support (P=0.021, B=0.06) were predictors of COVID-19 preventive behaviors. These constructs were able to predict 29% of changes in COVID-19 preventive behaviors. Among them, perceived barriers were the strongest predictor of preventive behaviors. Conclusion: Based on the predictors of COVID-19 preventive behaviors, it is suggested that policymakers, officials, and planners in the process of implementing behavioral change to improve COVID-19 preventive behaviors form strategies to increase mental sensitivity. In particular, they can use the risk of illness and inform families, as well as individuals, to improve their supportive role and self-efficacy to reduce barriers to performing preventive behavior.